Testing the Effect of COVID-19 on Herding Behavior in the Indonesian Islamic Stock Market - Purwanto Widodo (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to look at the herding behavior of shares of companies included in the JII (Jakarta Islamic Index). Observation period: January 5, 2009, to June 16, 2023, then divided into 3, namely the period before Covid-19, during Covid-19, and before - during Covid-19. Estimation of herding behavior using the Cross-Sectional Absolute Deviation (CSAD) model. The difference between this research and other studies is the model used. This study uses the Chang, Cheng & Khorana (2000) model which is modified by addingARCH - GARCH, to reveal the asymmetry effect. This study did not find herding behavior and the absence of the influence of Covid-19 on the movement of JII stocks, both before and during Covid-19. Theseresultsalso showthat investorshave rationalbehavior in making investmentdecisions. Investors on Jakarta Islamic Index stocks classified as Sharia principles are well educated. They have sufficient knowledge in managing information for decision-making, so they do not follow market consensus and make investment decisions based on available information. In addition, this study was able to reveal that the effect of positive shocks is greater when compared to negative shocks.